IJBlob: An ImageJ Library for Connected Component Analysis and Shape Analysis. (14th October 2013) - Wagner, Thorsten; Lipinski, Hans-Gerd
The IJBlob library is a free ImageJ library for connected component analysis. Furthermore, it implements several contour based shape features to describe, filter or classify binary objects in images. Other features are extensible by the IJBlob extension framework. Because connected component labeling is a fundamental operation in many image processing pipelines (e.g. pattern recognition), the library could be useful for many ImageJ projects. The library is written in Java and the recent release is available athttps://code.google.com/p/ijblob .